Site quality for Agave durangensis Gentry in the Mountain range of Registrillo, Durango - Loera-Gallegos, Héctor Manuel; Corral-Rivas, José Javier; Montiel-Antuna, Eusebio; Solis-Moreno, Raúl; Chávez-Simental, Jorge Armando; González- Cervantes, Guillermo (Revista Mexicana de Ciencias Agrícolas, 2018)
The Agave durangensis Gentry, is a natural resource that has been empirically exploited by the inhabitants of the semi-desert zone of the state of Durango. There are no scientific and regulatory elements that regulate or optimize the harvest of this product; therefore, having the present, provides the necessary tools for the correct use of agave. In the present investigation, the feasibility of five mathematical models was tested to determine the site quality of A. durangensis in the semi-desert zone of the Mountain range of Registrillo, Municipality of Durango, Mexico. The database used consisted of 204 pairs of dominant agaves in height-age, selected from 180 sampling sites in 1 000 m2 each, taken in the study area through systematic sampling. The adjustment of the mathematical models was performed by weighted non-linear regression methods to correct the problem of heterocedasticity of variance observed in the dominant-age height relationship. The results of the adjustment of the equations indicate that the Chapman-Richards model was the one that best determines site quality. Based on the analysis carried out, it is concluded that the use of site index models is feasible to classify the productivity of A. durangensis sites in the study area. The developed model provides compatible equations of site index and growth in dominant height.